A Novel Case Report of Impacted Mandibular Canine with Bifid Roots - Pallavi Raina; Santosh Kumar Goje (Journal of Integrated Health Sciences)
Mandibular canine impaction is less frequently encountered in orthodontic practice compared to maxillary canine impaction and poses a challenge to orthodontic treatment. A very rare incidental finding of an impacted mandibular canine having bifid roots is reported in this article. The case report highlights the key points to be kept in mind to diagnose the presence of bifid roots and canals. It also discusses how the finding of an impacted mandibular canine with bifid roots can influence orthodontic treatment planning. Since the diagnosis and the evaluation of the number of roots and canals are key to the success of root canal treatment, endodontic implications have been highlighted as well.